Coffee and cocoa value chains: Gender dynamics in Peru and Nicaragua - Gumucio, Tatiana; Yore, Hannah; Mello, Denyse; Loucel, Claudia (International Center for Tropical Agriculture, 2016)
The present report assesses women’s and men’s participation in coffee and cocoa value chains in Latin America in order to identify key considerations and next steps for the development of research, policy and practice on value chain upgrading for enhanced smallholder prosperity. In particular, the report analyzes the differential roles that women and men play and the benefits they perceive from their participation in coffee and cocoa value chains. It also considers the role of producer organizations in limiting or enhancing women’s participation and benefits from coffee and cocoa value chains. The report first reviews existing studies of gender and coffee and cocoa value chains in Latin American countries in order to identify principal trends; then, the paper focuses on Peru and Nicaragua as two country cases. In general, the report demonstrates that while factors such as labor burdens, access to productive resources, and socio-cultural norms can limit women’s participation in and returns from coffee and cocoa value chains in comparison to that of men, varied initiatives have sought to address these restricting conditions via producer organizations. The extent and circumstances of their success in advancing gender equality in coffee and cocoa value chains will be an important area for future analysis.